THE PARADOX OF ENGLISH LEARNING: A QUALITATIVE STUDY OF LIMITED SPEAKING ABILITY DESPITE LONG-TERM ENGLISH INSTRUCTION AMONG UNIVERSITAS DHARMAS INDONESIA STUDENTS - Lia Faridatul Ulfa; Martiya Nurni Khairita; Zumrotun Lutfiah (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
Speaking ability is considered one of the most important indicators of successful English learning, especially in English as a Foreign Language (EFL) contexts. However, many students still experience difficulties in speaking English despite having received formal English instruction for many years. This study aims to explore the factors contributing to students’ limited speaking ability after long-term English learning experiences. This study employed a qualitative research design using a descriptive qualitative approach. The participants were university students from Universitas Dharmas Indonesia who were non-English major students and had learned English for several years through formal education. Data were collected through semi-structured interviews and documentation, and the data were analyzed using qualitative data analysis techniques consisting of data reduction, data display, and conclusion drawing. The findings revealed that long-term English instruction did not automatically guarantee effective speaking ability. Students continued to experience speaking difficulties due to several internal and external factors. Internal factors included limited vocabulary mastery, pronunciation difficulties, speaking anxiety, fear of making mistakes, lack of confidence, and low motivation. Meanwhile, external factors involved teachers-centered teaching methods, limited speaking practice, limited exposure to English, unsupportive classroom environments, and lack of communicative activities. The findings also indicate a paradox between the length of English learning and students’ actual speaking performance. Although students had learned English for many years, their speaking ability remained limited because learning experiences were often dominated by theoretical knowledge rather than meaningful communication practice. Therefore, English learning should provide more opportunities for active language use, interaction, and communicative activities to supports students’ speaking development.